Penerapan Rasch Model untuk Validasi Copenhagen Burnout Inventory (CBI) Versi Indonesia - Putri, Grace Angeline Nikita; Yudiarso, Ananta (Syntax Literate, 2025)
This study aims to validate the Copenhagen Burnout Inventory (CBI) measuring instrument in the context of workers in Indonesia using the Rasch Model through Winsteps 5.0 analysis software. This method provides a comprehensive approach to measure burnout dimensions accurately and consistently. Data was collected from 377 workers in various sectors in Indonesia. The validation process involved Rasch analysis to evaluate item fit, individual response fit, and measurement accuracy. Test results showed that the CBI has good validity and reliability, thus providing empirical support for the suitability of the CBI in measuring burnout levels among workers in Indonesia more accurately and consistently.